Managing patients with myelofibrosis and thrombocytopenia. Issue 3 (4th March 2022) - Yilmaz, Musa; Verstovsek, Srdan
ABSTRACT: Introduction: Given the progressive nature of myelofibrosis, the incidence of thrombocytopenia increases over time. Furthermore, approved drugs ruxolitinib and fedratinib, induce thrombocytopenia. Hence, treatment of myelofibrosis patients with low platelet counts is an unmet need. Areas Covered: This review summarizes the current and emerging treatment options available for patients with myelofibrosis and thrombocytopenia. In the first section of this review, we summarized the use of JAK inhibitors in patients with thrombocytopenia, and in the second part, we focused on use of therapies other than JAK Inhibitors such as steroids, immunomodulatory agents, androgens and other novel agents. Expert Opinion: Up to 25% of patients with myelofibrosis have platelet counts below 100, 000 at presentation. Patients with thrombocytopenia are more likely to be anemic and PRBC transfusion-dependent, as well as have high-risk disease characteristics and a poor overall survival rate. Among all JAK inhibitors studied in phase 3 clinical trials, pacritinib seems not to induce significant thrombocytopenia while maintaining a good spleen response. Severe thrombocytopenia is a major impediment to myelofibrosis therapy, and more research, particularly on novel therapeutic agents aimed at cytopenic patient populations, is needed.